How to Improve the Effectiveness of School Archives Management in the Industrial Revolution Era 4.0? - Oktarina, Nina; Widodo, Joko; ., Murwatiningsih; Suryanto, Edy (KnE Social Sciences, 2020)
The 4.0 era of industrial revolution has impacts on all aspects of life Including management aspects of school administration. Fast and accurate information needs in education require schools to integrate ICT in archives management. This study aims to describe and analyze the effectiveness of school records management. It is a qualitative the study. The object of this the study is a senior high school at Semarang city. Data collection techniques used interviews, observation and documentation. The results of the study Showed that school archives management has not been effective. It is the caused by the lack of ability of archives management officers, archival inadequate infrastructure and the school does not have standards for school operational procedure archives management. Keywords: Effectiveness, Management, Archives, Industrial Revolution 4.0